Impaired COMMD10-Mediated Regulation of Ly6Chi Monocyte-Driven Inflammation Disrupts Gut Barrier Function - Mouhadeb, Odelia; Ben Shlomo, Shani; Cohen, Keren; Farkash, Inbal; Gruber, Shlomo; Maharshak, Nitsan; Halpern, Zamir; Burstein, Ezra; Gluck, Nathan; Varol, Chen (Frontiers in Immunology, 2018)
Ly6Chi monocyte tissue infiltrates play important roles in mediating local inflammation, bacterial elimination and resolution during sepsis and inflammatory bowel disease (IBD). Yet, the immunoregulatory pathways dictating their activity remain poorly understood. COMMD family proteins are emerging as key regulators of signaling and protein trafficking events during inflammation, but the specific role of COMMD10 in governing Ly6Chi monocyte-driven inflammation is unknown. Here we report that COMMD10 curbs canonical and non-canonical inflammasome activity in Ly6Chi monocytes in a model of LPS-induced systemic inflammation. Accordingly, its deficiency in myeloid cells, but not in tissue resident macrophages, resulted in increased Ly6Chi monocyte liver and colonic infiltrates, elevated systemic cytokine storm, increased activation of caspase-1 and-11 in the liver and colon, and augmented IL-1 production systemically and specifically in LPS-challenged circulating Ly6Chi monocytes. These inflammatory manifestations were accompanied by impaired intestinal barrier function with ensuing bacterial dissemination to the mesenteric lymph nodes and liver leading to increased mortality. The increased inflammasome activity and intestinal barrier leakage were ameliorated by the inducible ablation of COMMD10-deficient Ly6Chi monocytes. In consistence with these results, COMMD10-deficiency in Ly6Chi monocytes, but not in intestinal-resident lamina propria macrophages, led to increased IL-1 production and aggravated colonic inflammation in a model of DSS-induced colitis. Finally, COMMD10 expression was reduced in Ly6Chi monocytes and their corresponding human CD14hi monocytes sorted from mice subjected to DSS-induced colitis or from IBD patients, respectively. Collectively, these results highlight COMMD10 as a negative regulator of Ly6Chi monocyte inflammasome activity during systemic inflammation and IBD.